DIAGNOSTICS AND TREATMENT OF NEURAL DISEASES IN CHILDREN USING ARTIFICIAL INTELLIGENCE AND MODERN COMPUTER SYSTEMS - Abduraimov Abdulaziz Umidjon o‘g‘li; Oxunjonov Bunyodbek Baxromboy o‘g‘li (Bright Mind Publishing, 2025)
This scientific article discusses the use of artificial intelligence and modern computer systems in the diagnosis and treatment of neuralgic diseases in children. Nowadays, the use of information technologies and artificial intelligence systems in the field of medicine is of great importance in maintaining human health. These technologies are especially effective in the early detection of nervous system diseases in children. The article discusses the main causes of neuralgic diseases, the advantages of artificial intelligence systems in their detection, diagnostic processes and treatment methods implemented using computer programs. It also shows the possibilities of creating a treatment program tailored to the individual condition of the child using modern technologies.
Keywords: children, neurology, artificial intelligence, diagnostics, treatment, computer systems, medical technologies.